2009
DOI: 10.1080/17482960802267480
|View full text |Cite
|
Sign up to set email alerts
|

Enteral and parenteral nutrition in the later stages of ALS: An observational study

Abstract: Current practice guidelines state that enteral feeding should be proposed and provided whenever ALS patients show significant dysphagia and/or weight loss. Percutaneous endoscopic gastrostomy (PEG) is usually available at ALS centres, but this method is not indicated in the case of patients with severe respiratory impairment. We undertook a study to assess the feasibility of applying home parenteral nutrition (PN) to ALS patients with respiratory insufficiency, to assess the complications and survival times af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
0
13
0
7
Order By: Relevance
“…Diaphragmatic weakness causes a “high‐riding” stomach, in which the stomach lies under the ribs, which can increase the difficulty of PEG placement 37 . Nasogastric tube feedings are indicated only for short‐term nutrition support due to the high risk of aspiration and because of their uncomfortable and embarrassing nature 48 . Nasogastric tubes increase oropharyngeal secretions and can cause nasopharyngeal discomfort or even ulceration 48 , 49 .…”
Section: Risk Factors For Malnutrition In Amyotrophic Lateral Sclerosmentioning
confidence: 99%
See 3 more Smart Citations
“…Diaphragmatic weakness causes a “high‐riding” stomach, in which the stomach lies under the ribs, which can increase the difficulty of PEG placement 37 . Nasogastric tube feedings are indicated only for short‐term nutrition support due to the high risk of aspiration and because of their uncomfortable and embarrassing nature 48 . Nasogastric tubes increase oropharyngeal secretions and can cause nasopharyngeal discomfort or even ulceration 48 , 49 .…”
Section: Risk Factors For Malnutrition In Amyotrophic Lateral Sclerosmentioning
confidence: 99%
“…Nasogastric tube feedings are indicated only for short‐term nutrition support due to the high risk of aspiration and because of their uncomfortable and embarrassing nature 48 . Nasogastric tubes increase oropharyngeal secretions and can cause nasopharyngeal discomfort or even ulceration 48 , 49 . Postpyloric feeding tubes may be indicated if intolerance is present with gastric feedings, such as in the presence of severe gastroesophageal reflux disease, gastroparesis, or gastrectomy 50 …”
Section: Risk Factors For Malnutrition In Amyotrophic Lateral Sclerosmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown, however, that parenteral nutrition is superior in specific circumstances and for the intensive supply of specific micronutrients [4]. Although several clinical trials have compared the nutritional and clinical aspects of enteral versus parenteral nutrition in various clinical settings [5,6], these modalities have not been compared in the postoperative care of patients after laryngeal or pharyngeal cancer surgery. Surgery for these cancers involves extensive resection and surgical damage to tissues critical in the normal swallowing mechanism, making postoperative swallowing rehabilitation inevitable and causing the requirement for alternative nutritional support for a certain period of time.…”
mentioning
confidence: 99%